Spindle epithelial tumor with thymus-like elements (SETTLE): a diagnostic challenge with distinct therapeutic implication; case report - Prerna Chadha; Meenakshi Kamboj; Sunil Pasricha; Vikas Arora; Vishal Yadav; Manoj Gupta; Anurag Mehta (BMC, 2024)
Abstract Spindle epithelial tumor with thymus-like elements (SETTLE) is a rare malignant neoplasm of the thyroid gland which is believed to arise from intrathyroidal thymic tissue. It predominantly affects young adults and children presenting with a thyroid mass of variable duration and rarely occurs in adults. It has a high overall survival with a tendency for delayed metastasis. SETTLE is a biphasic lobulated tumor composed of spindle shaped cells along with glandular formations seen on histopathological examination. Despite its typical morphology it is commonly misdiagnosed on histopathology due to its rarity and overlapping morphology with other close mimics such as a carcinoma, synovial sarcoma and thymoma. Herein we report such a case occurring in a middle aged female presenting with a neck mass. She had an initial diagnosis of metastatic poorly differentiated squamous cell carcinoma possibly with an orophayngeal primary in view of co expression of CK, p40 and p16 on immunohistochemistry. The patient underwent surgical resection with modified neck dissection. On review at our hospital it was diagnosed as SETTLE and she remains disease free after a follow-up period of 1 year. Diligent histopathological examination espoused with a judicious panel of IHC markers in conjunction with clinicoradiological findings forms the mainstay of diagnosis. Diffuse and strong p16 immunoexpression has not been documented or evaluated in literature so far, and needs to be explored for its diagnostic utility in this rare entity.